2018
DOI: 10.3892/or.2018.6675
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer is associated with methylation and expression of the a disintegrin and metalloproteinase domain�33 (ADAM33) gene affected by endocrine‑disrupting chemicals

Abstract: A disintegrin and metalloproteinase domain 33 (ADAM33) gene is a transmembrane glycoprotein that mediates changes in cell adhesion and plays an important role in cancer progression. Since bisphenol A (BPA) and phthalates are epigenetically toxic, the purpose of this study was to examine whether BPA and phthalate metabolites, including monoethyl phthalate (MEP), mono‑n‑butyl phthalate (MBP), mono‑isobutyl phthalate (MIBP), mono(2‑ethylhexyl) phthalate (MEHP), mono(2‑ethyl‑5‑hydroxyhexyl) phthalate (MEHHP), mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Compared to nonusers, the concentration of MiBP is higher in users of perfume 35 , 38 and MEOHP is higher in bottled water 38 . Our previous study found that MEHHP, MECPP, MEOHP, and Σ 4 DEHP were positively associated with increased intron 1 methylation level and gene expression in ADAM33 gene and the phenomenon may be related to decreased breast cancer risk 39 . Two studies and a multiethnic cohort study in whites observed an non-significant negative association between MEOHP and breast cancer 13 , 14 , 40 ; a prospective study and an Alaska study showed that MEOHP were not associated with breast cancer 12 , 15 .…”
Section: Discussionmentioning
confidence: 93%
“…Compared to nonusers, the concentration of MiBP is higher in users of perfume 35 , 38 and MEOHP is higher in bottled water 38 . Our previous study found that MEHHP, MECPP, MEOHP, and Σ 4 DEHP were positively associated with increased intron 1 methylation level and gene expression in ADAM33 gene and the phenomenon may be related to decreased breast cancer risk 39 . Two studies and a multiethnic cohort study in whites observed an non-significant negative association between MEOHP and breast cancer 13 , 14 , 40 ; a prospective study and an Alaska study showed that MEOHP were not associated with breast cancer 12 , 15 .…”
Section: Discussionmentioning
confidence: 93%
“…Conversely, we discovered a potential association between increased urinary concentration of BPA and BC. Furthermore, MEP and MBP, both phthalate metabolites were negatively correlated with ADAM33 expression [ 106 ].…”
Section: Adams In Breast Cancermentioning
confidence: 99%
“…What’s interesting is that the co-exposure can produce antagonistic effect. Moreover, other authors found that PAEs metabolites could upregulate the expression of disintegrin and metalloproteinase domain 33 (ADAM33), which plays a significant role in reducing BC risk ( 215 ).…”
Section: Introductionmentioning
confidence: 99%